Study Of Intra Testicular Regulations Of Spermatogenesis Differentiation By Ex-vivo Approach - Adaika, A.; Barenton, B.; Durand, P. (University of Eloued جامعة الوادي, 2010)
The aim of this work is to study the regulation of intratesticular during spermatogenesis ex vivo. To highlight the progress of spermatogenesis ex vivo, we developed two cell culture systems of seminiferous tubules to study the role of local factors that control the proliferation and differentiation of male germ cells. Our studies are based on two main techniques: RT-PCR and RNA extraction to examine changes in the expression of some growth factors in the culture of seminiferous tubules as the SCF, c- Kit and TGFß. The results show, using RT-PCR, that expression of SCF, c-Kit and TGFb is probably not involved in the alterations of spermatogenesis ex vivo. Indeed, their expressions are not modified during three weeks of culture, and their expressions depend on the proportion of cells where they are expressed. Our results also show that clusterin is a marker of Sertoli cells in the culture of seminiferous tubules and its expression is not altered by the presence of germ cells.
Articale in Journal of fundamental and Applied Sciences Vol. 02 N. 02
Keywords: Spermatogenesis, Sertoli cells, RT-PCR, SCF, c-Kit, TGFß, clusterin